Activation of Cannabinoid Receptor 2 Ameliorates DSS-Induced Colitis through Inhibiting NLRP3 Inflammasome in Macrophages - Ke, Ping; Shao, Bo-Zong; Xu, Zhe-Qi; Wei, Wei; Han, Bin-Ze; Chen, Xiong-Wen; Su, Ding-Feng; Liu, Chong (PloS one, 2016)
Activation of cannabinoid receptor 2 (CB2R) ameliorates inflammation, but the underlying mechanism remains unclear. In the present study, we examined whether activation of CB2R could suppress the nucleotide-binding domain and leucine-rich repeat protein 3 (NLRP3) inflammasome. In peritoneal macrophages isolated from C57BL/6 mice, LPS/DSS challenge for 24 h increased the expression of the components of NLRP3 inflammasome NLRP3, Casp-1 p20/Casp-1 p45 ratio, proIL-1β and IL-1β and also enhanced autophagy (LC3-II/LC3-I ratio, Beclin-1 and SQSTM1). Pretreatment of peritoneal macrophages with HU 308, a selective CB2R agonist, attenuated LPS/DSS-induced NLRP3 inflammasome activation, but further enhanced autophagy. In comparison with wild-type (WT) control, peritoneal macrophages from CB2R knockout (KO) mice had more robust NLRP3 inflammasome activation and attenuated autophagy upon LPS/DSS challenge. Knockdown autophagy-related gene 5 (Atg5) with a siRNA in peritoneal macrophages attenuated the inhibitory effects of HU 308 on LPS/DSS-induced NLRP3 inflammasome activation in vitro. In vivo, HU308 treatment attenuated DSS-induced colitis mice associated with reduced colon inflammation and inhibited NLRP3 inflammasome activation in wild-type mice. In CB2R KO mice, DSS-induced inflammation and NLRP3 inflammasome activation were more pronounced than those in WT control. Finally, we demonstrated that AMPK-mTOR-P70S6K signaling pathway was involved in this CB2R-mediated process. We conclude that activation of CB2R ameliorates DSS-induced colitis through enhancing autophagy that may inhibit NLRP3 inflammasome activation in macrophages.